THE THEOTOKOS AS PNEUMATOPHORA - B. T. Bilaniuk, Petro (Journal of Dharma, 1980)
An interest in linking Mariology and Pneumatology is of recent date. It is only after the Second Vatican Council that serious attempts have been made to develop Mariology within the pneumatological context and to rethink the mystery of Mary the Mother of God within the mystery of the Holy Spirit and His activity in the history of salvation and the Church.' In all likelihood, this coincides with the general renewal of both theological and spiritual interest in the Holy Spirit among most of the Christian Churches and communities of our day. There is a general feeling about the inadequacy of the different types of theologies of the past which were either too frigid and subservient to the institutional view of the theology and the Church, or one-sided and concentrated upon the Christological, soteriological, or ecclesiological aspects only. Pneumatology has usually been a brief and inadequate corollary or even a footnote to the doctrine of the Most Holy Trinity, Soteriology, or Ecclesiology."